Effect of Gymnasticspregnancy Results in Decreasing Anxiety Levels in Primigravida Pregnant Women Trimester III - Soleha, Marchatus; Zelharsandy, Vika Tri; Anggeriani, Rini; Sepiwiryanti, Wika (GLOBAL HEALTH SCIENCE GROUP, 2024)
Anxiety in facing childbirth is a mixed feeling, namely feelings of happiness full of hope accompanied by feelings of anxiety, fear, fear of death, birth trauma, and feelings of guilt/sin, worry, stress, unease, muscle tension, difficulty sleeping, anxiety. ongoing feelings that don't go away, and feelings of panic. Based on the results of a preliminary study conducted by researchers in January 2023 by interviewing 10 pregnant women in the third trimester at the Poskesdes Epil sub-district. Lais found that the level of anxiety of mothers facing the birth process was still high, eight out of ten mothers said they felt afraid before giving birth. This study aims to determine the effect of pregnancy exercise on reducing anxiety levels in third-term primigravida pregnant women at the Epil village health post, Lais sub-district, Musi Banyuasin Regency. This research uses quantitative methods using a pre-experimental design with an approach (One Group Pre-Post Test Design). The population of this study were all third trimester primigravida pregnant women who had their pregnancy checked at the Epil village health post, Kec. Lais as many as 40 people. The sample in this study was 20 respondents, using a purposive sampling technique. The analysis used was the paired sample t-test. The results of the research: Before carrying out pregnancy exercises, the respondents' anxiety levels were in the category of mild anxiety and moderate anxiety. After carrying out pregnancy exercises, the respondents' anxiety levels were in the categories of not anxious and mild anxiety. There was a significant difference between respondents before doing pregnancy exercises and after doing pregnancy exercises. (P Value = 0.000). There are differences before doing pregnancy exercises and after doing pregnancy exercises.